2014
DOI: 10.1007/s10201-014-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

Interference competition in a planktivorous fish (Rutilus rutilus) at different prey densities and temperatures

Abstract: The effect of interference competition can be assessed by comparing the capture rate of a predator foraging alone with that of the predator within a group. Since such an effect could be prey density dependent, a constant density of prey must be maintained while assessing this effect, irrespective of the elimination of prey by predation. However, when studying a predator-harvester, such as a planktivorous fish, which collects zooplankton at a rate of up to 1 prey s -1 , instantaneous replacement of each consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This notion is supported by the high number of fish leaving the high-prey-density tank after the first minutes of each feeding session, despite the prey density still being much higher than in the neighbouring region. Neither the earlier observations of rudd behaviour (Maszczyk et al 2014 ), nor the video recording from the two experimental sections have ever suggested that the permanent appearance of fish in the other low-prey-density locations was due to interference competition resulting from either passive competition or aggressive behaviour in the high-prey-density tank that would further increase with the arrival of new individuals into the patch of prey. This is why the cause may instead stem from perceptual constraints such as weak memory, insufficient knowledge of the pattern of prey distribution, and an insufficient ability to accurately assess resource distribution (Abrahams 1986 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This notion is supported by the high number of fish leaving the high-prey-density tank after the first minutes of each feeding session, despite the prey density still being much higher than in the neighbouring region. Neither the earlier observations of rudd behaviour (Maszczyk et al 2014 ), nor the video recording from the two experimental sections have ever suggested that the permanent appearance of fish in the other low-prey-density locations was due to interference competition resulting from either passive competition or aggressive behaviour in the high-prey-density tank that would further increase with the arrival of new individuals into the patch of prey. This is why the cause may instead stem from perceptual constraints such as weak memory, insufficient knowledge of the pattern of prey distribution, and an insufficient ability to accurately assess resource distribution (Abrahams 1986 ).…”
Section: Discussionmentioning
confidence: 86%
“…The results of this study also show that the optimal exploitation of patches of zooplankton prey leads to their rapid annihilation. This occurs as a result of the combined effects of the predator’s functional response [an increase in the capture rate up to the highest values ever observed in planktivorous fish in laboratory and field studies of 0.8 prey s −1 (Bartosiewicz and Gliwicz 2011 )] and the predator’s rapid numerical response in space, when the decline in prey concentration and interference within the overexploited patch of prey may encourage fish to swim faster to compensate for the reduced encounter rate, thus increasing the probability of mechanical interference with one another (Persson 1986 ; Maszczyk et al 2014 ). As a consequence, the role of aggregating in zooplankton as an antipredation defence against fish predation (Pijanowska and Kowalczewski 1997 ) becomes questionable, and this is the point where the results of this study meet the theoretical approach focused on the stabilizing role of predators in their top–down regulation of prey density and distribution in space and time (Morozov et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such an experimental design has been conducted only in a few systems due to its strong experimental limitations. Two studies, one using a crab‐bivalve system and the other using a roach‐daphnia system, excluded food exploitation (Maszczyk et al., 2014; Smallegange et al., 2006). Specifically, they prevented food depletion by replenishing instantaneously any consumed food items.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include more efficient foraging (Day et al, 2001 ; Hintz & Lonzarich, 2018 ) and swimming (Marras et al, 2015 ; Miller & Gerlai, 2011 ), as well as better protection from predators (e.g., see Ioannou, 2017 ). The disadvantages include enhanced conspicuousness to predators (Botham et al, 2005 ), elevated parasitism (Poulin, 1999 ) and resource competition within the group (Maszczyk et al, 2014 ). These costs and benefits may vary with group size.…”
mentioning
confidence: 99%